PENGARUH LATIHAN BOX JUMP TERHADAP POWER OTOT TUNGKAI PADA SISWA SMK NEGERI 2 PEKANBARU YANG MENGIKUTI EKSTRAKURIKULER ATLETIK NOMOR LOMPAT JAUH (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is the lack of ability to do long jumps for students at SMKN 2 Pekanbaru who take long jump extracurriculars which is caused by a lack of field practice and only emphasizes long jump theory. The purpose of this study was to determine the effect of box jump exercise on leg muscle power in students of SMK Negeri 2 Pekanbaru who participated in the long jump athletic extracurricular. The population in this study were students of SMKN 2 Pekanbaru who took part in the long jump extracurricular using a total sampling technique with a total sample of 10 students. This type of research is experimental, using a pre-test-post-test design using a standing board jump test instrument, using the t-distribution data analysis technique. Based on the analysis carried out, the t_count value between the initial test and the final test of box jump exercise on leg muscle power with t_table at a significant level of 0.05 with degrees of freedom N – 1 (9) indicates that the value of t_count (5.818) > t_(table )(1.833 Thus, it can be concluded that the hypothesis which states that there is an effect of box jump exercise on leg muscle power in SMK Negeri 2 Pekanbaru students who take part in the long jump athletic extracurricular.Key Words: Box Jum Exercise, Limp Muscle Power,Jumping